Serious game design for terengganu brassware craft heritage - Wan Malini, Wan Isa; Zin, N.A.M; Rosdi, F; Sarim, H.M (2019)
Serious games are increasingly used in various fields such as cultural heritage. The Terengganu brassware craft is becoming extinct due to several factors such as lack of interest from the younger generation and lack of apprentice. The use of serious games in cultural heritage is significant to attract and engage the younger generation to preserve and conserve the cultural heritage. In order to develop an effective serious game, a good design is required. This study focused on the design phase to develop a serious game for Terengganu brassware craft cultural heritage. There are several activities involved in designing this game including the preparation of game design document, level design, character design and game interface design. The outcome of this design is a low fidelity prototype - a storyboard using sketching technique. The testing phase would be carried out on the low fidelity prototype to ensure that the design meets the requirements of the target user.